Cytokine sensitivity screening highlights BMP4 pathway signaling as a therapeutic opportunity in ER+ breast cancer. Issue 2 (30th August 2018) - Shee, Kevin; Jiang, Amanda; Varn, Frederick S.; Liu, Stephanie; Traphagen, Nicole A.; Owens, Philip; Ma, Cynthia X.; Hoog, Jeremy; Cheng, Chao; Golub, Todd R.; Straussman, Ravid; Miller, Todd W.
ABSTRACT: Despite the success of approved systemic therapies for estrogen receptor α (ER)‐positive breast cancer, drug resistance remains common. We hypothesized that secreted factors from the human tumor microenvironment could modulate drug resistance. We previously screened a library of 297 recombinant‐secreted microenvironmental proteins for the ability to confer resistance to the anti‐estrogen fulvestrant in 2 ER + breast cancer cell lines. Herein, we considered whether factors that enhanced drug sensitivity could be repurposed as therapeutics and provide leads for drug development. Screening data revealed bone morphogenic protein (BMP)4 as a factor that inhibited cell growth and synergized with approved anti‐estrogens and cyclin‐dependent kinase 4/6 inhibitors (CDK4/6i ). BMP4‐mediated growth inhibition was dependent on type I receptor activin receptor‐like kinase (ALK)3‐dependent phosphorylation (P) of mothers against decapentaplegic homolog (SMAD/P‐SMAD)1 and 5, which could be reversed by BMP receptor inhibitors and ALK3 knockdown. The primary effect of BMP4 on cell fate was cell‐cycle arrest, in which RNA sequencing, immunoblot analysis, and RNA interference revealed to be dependent on p2i WAF1/Cip1 upregulation. BMP4 also enhanced sensitivity to approved inhibitors of mammalian target of rapamycin complex 1 and CDK4/6 via ALK3‐mediated P‐SMAD1/5 and p21 upregulation in anti‐estrogen‐resistant cells. Patients bearing primary ER + breast tumors, exhibiting a transcriptomic signature of BMP4 signaling, had improved disease outcome following adjuvant treatment with anti‐estrogen therapy, independently of age, tumor grade, and tumor stage. Furthermore, a transcriptomic signature of BMP4 signaling was predictive of an improved biologic response to the CDK4/6i palbociclib, in combination with an aromatase inhibitor in primary tumors. These findings highlight BMP4 and its downstream pathway activation as a therapeutic opportunity in ER + breast cancer.—Shee, K., Jiang, A., Varn, F. S., Liu, S., Traphagen, N. A., Owens, P., Ma, C. X., Hoog, J., Cheng, C., Golub, T. R., Straussman, R., Miller, T. W. Cytokine sensitivity screening highlights BMP4 pathway signaling as a therapeutic opportunity in ER + breast cancer. FASEB J. 33, 1644–1657 (2019). www.fasebj.org